Investigation of Gold Ore Deposits in Brgy. Mainit, Iligan City and Pre-Testing Using Micron Mill Wave Table - Itao, Gevelyn; Enerio, R-Jay; Nacalaban, Jellian Paula; Abid, Axzel Rose (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2022)
A potential gold ore deposit discovered on the mountain region of Iligan City, specifically in the Mainit area was inspected. The current artisanal gold mining and extraction was also assessed. It was found out that the locals, if not selling the ore as is, were using mercury amalgamation as an extraction process. Ore sample was collected in the area and was subjected to characterization tests with specific gravity of 3.073 categorizing it as moderately heavy, 20.58 Bond Work Index meaning a very hard ore, and liberation size observation through microscopy is at 150 microns. XRD and XRF analysis indicates that silica in the form of quartz is the most abundant element having 71.34%. After characterizing, the ore was then concentrated using the Micron Mill Wave Table. Gold concentration was done on three different particle mesh sizes, 40, 100 and 200, respectively. Concentration was done on the Micron Mill Wave Table’s default parameters i.e. elevation, ore to water ratio, and overall feeding time. Products from the concentration were then analysed using fire as saying. From the preliminary testing conducted, results showed that highest gold recovery was obtained at -100 mesh with 58.30% and at table inclination of 2.35°-3.28° with 69.60%. The initial results gathered for both production runs suggest that possible higher gold recovery of the Mainit ore through concentration using Micron Mill Wave Table can be obtained with particle size -100 mesh at a higher table inclination.